A case study on travel information from social network - Focus in Facebook and blogs in Malaysia - Zulkefli, N.A.B.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Due to the rapidly growing of social network media such as Facebook, Twitter and Blog, the rich contexts and sharing information of human activities are also explosive increase. Lately, many people used social media as a platform to exchange and share information such as education, lifestyle, recipes and medical treatment. Tourism is one of the most popular topics shared in Facebook and Blog. To explore details about the travel data, we created a survey to study the users sharing behavior. This paper presents the case study of travel sharing information in social network and the travel data collection in Place of Interest (POI) in Malaysia. Â© 2014 IEEE.